A mild and facile synthesis of aryl and alkenyl sulfides via copper-catalyzed deborylthiolation of organoborons with thiosulfonates. Issue 93 (8th October 2015) - Yoshida, Suguru; Sugimura, Yasuyuki; Hazama, Yuki; Nishiyama, Yoshitake; Yano, Takahisa; Shimizu, Shigeomi; Hosoya, Takamitsu
Abstract : A simple, efficient, and odorless deborylthiolation of aryl- and alkenylborons with thiosulfonates has been achieved under mild conditions using a copper catalyst. Abstract : An efficient deborylthiolation of aryl- and alkenylborons with thiosulfonates has been achieved under mild conditions using a copper catalyst. All steps of the experimental process were free from unpleasant odors. The mild reaction conditions as well as ready availability of boron compounds and thiosulfonates enabled easy access to an array of sulfides, including those bearing sensitive functional groups.